Silicon-oriented regio- and enantioselective rhodium-catalyzed hydroformylation - Cai You; Xiuxiu Li; Yuhong Yang; Yu-Sheng Yang; Xuefeng Tan; Shuailong Li; Biao Wei; Hui Lv; Lung-Wa Chung; Xumu Zhang (Nature Communications, 2018)
Hydroformylation of 1,2-disubstituted alkenes usually occurs at the α position of the directing heteroatom. Here, the authors report the asymmetric rhodium-catalyzed hydroformylation of 1,2-disubstituted alkenylsilanes with excellent regioselectivity at the β position (relative to the silicon heteroatom) and enantioselectivity.